Winnick's Case for a Changing Attitude Toward Housing: Reply - Winnick, Louis (Quarterly Journal of Economics, 1956)
Journal Article Winnick's Case for a Changing Attitude Toward Housing: Reply Get access Louis Winnick Louis Winnick New York City Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 70, Issue 2, May 1956, Pages 319–323, https://doi.org/10.2307/1884272 Published: 01 May 1956